Dynamics of hydrogen-bonded end groups in bulk polymers revealed by solid-state NMR spectroscopy relaxation dispersion experiments - Sophia Thiele; Christopher J. G. Plummer; Laura Piveteau; Holger Frauenrath (Communications Chemistry)
Abstract The dynamic nature of supramolecular networks of telechelic polymers offers new avenues for the design of novel materials with enhanced melt strength and extensibility, increased energy at break, or self-healing properties. However, monitoring the kinetics of the underlying molecular-level scission-reaggregation events remains challenging, particularly in high-molar-mass polymers in the bulk state. Here, we employ solid-state 1H NMR spectroscopy relaxation dispersion experiments to investigate the aggregation-scission dynamics in poly(ε-caprolactone) modified with oligopeptide end groups that form one-dimensional hydrogen-bonded aggregates. We have successfully determined the timescale of end-group dissociation directly and independently of any relaxation of the polymer segments at different temperatures in the bulk semi-crystalline and melt state. This site-specific, non-destructive method is applicable to entangled, high-molar-mass polymers without chemical modifications or modeling, provides critical insight into the dynamics of supramolecular networks in the bulk state, and promises to be a valuable tool for the directed development of next-generation functional materials.